Economic Evaluation of Sustainable Development - Thomas, Vinod (Springer Nature, 2019)
This book is open access under a CC BY 4.0 license. This book presents methods to evaluate sustainable development using economic tools. The focus on sustainable development takes the reader beyond economic growth to encompass inclusion, environmental stewardship and good governance. Sustainable Development Goals (SDGs) provide a framework for outcomes. In illustrating the SDGs, the book employs three evaluation approaches: impact evaluation, cost-benefit analysis and objectives-based evaluation. The innovation lies in connecting evaluation tools with economics. Inclusion, environmental care and good governance, thought of as "wicked problems", are given centre stage. The book uses case studies to show the application of evaluation tools. It offers guidance to evaluation practitioners, students of development and policymakers. The basic message is that evaluation comes to life when its links with socio-economic, environmental, and governance policies are capitalized on.